Development and Implementation of a Highly Sensitive Method for Analyzing Chemical Forms of Iron Using XAFS Measurements - Iori Mishima; Keiichi Kubota; Tomohide Watanabe (Journal of Water and Environment Technology)

(untitled)
The chemical forms of iron significantly influence the dynamics of nutrients and biological productivity in the water environment. The most common oxidized form of iron, Fe(III), forms insoluble compounds such as goethite (α-FeOOH) in its oxidized state. Especially, Fe(III) compounds readily adsorb phosphate ions, effectively preventing phosphorus from dissolving into the water. Conversely, in a reductive environment, the reduction of Fe(III) to Fe(II) can release previously adsorbed phosphorus. These interactions are considered crucial for proper water quality management and environmental conservation, with a focus on the chemical forms of iron. In this study, highly sensitive methods for analyzing the chemical forms of iron using X-ray absorption fine structure (XAFS) measurements were developed. Four pretreatment methods were evaluated, and anaerobic drying was found to most effectively preserve the reduced iron state. Pattern fitting techniques were applied to sediment samples, and it was shown that the method could accurately describe the iron forms in these samples. These findings are considered to contribute to the understanding of iron’s role in nutrient cycling and its broader impact on water environments.